What is a Lollard? Dissent and Belief in Late Medieval England. By J. Patrick Hornbeck - Tanner, Norman (The journal of theological studies, 2011)
‘What is’ rather than ‘Who was’ in the title reveals the basic intent of this monograph. Thus the purpose is historiographical more than historical: to investigate the criteria by which men and women came to be called Lollards and the de facto diversity of the individuals so styled. Attention is given to the use of the description ‘Lollard’ during the period when living individuals were so named, the late Middle Ages, and in the writings of the first great historian of Lollardy, John Foxe. But the main focus is upon recent historiography, from the five most influential writers—K. B. McFarlane, A. G. Dickens, J. A. F. Thomson, Anne Hudson, and Margaret Aston—onwards. Though most—but not all—of these recent writers who appear in the book are included in the index (pp.